PENGARUH LIKUIDITAS, LEVERAGE , PROFITABILITAS, OPERATINGCAPACITY, BIAYA AGENSI MANAJERIAL TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Farrah Anggita Nurmaliani, 15.05.52.0325; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2019)
This study aims to test and analyze the factors that influence financial distress in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. Independent variables consist of Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA), Total Asset Turnover (TATO), and Managerial Agency Costs (BAM) while the dependent variable is Financial Distress (FD). This study uses secondary data. The sampling method is purposive sampling. The analysis used was descriptive statistics, Feasibility Model, overall test model, Chi square test, Cox test and Snell's R Square and Nagkerkke; R Square, 2x2 classification table, logistic regression analysis, using SPSS 19 for Windows. The results showed that liquidity does not affect Financial Distress, Leverage has a significant positive effect on Financial Distress, Profitability has a significant negative effect on Financial Distress, Operating Capcity has a negative effect on Financial Distress, Managerial Agency Costs do not affect financial distress.